EARLY PALEOZOIC PALEOMAGNETISM OF EAST KAZAKHSTAN: IMPLICATIONS FOR PALEOLATITUDINAL DRIFT OF TECTONIC ELEMENTS WITHIN THE URAL-MONGOL BELT - Collins A.Q.; Bazhenov M.L.; Degtyarev K.E.; Levashova N.M.; Van der Voo R. (My University, 2003)
Conflicting paleogeographic reconstructions of the Ural–Mongol fold belt have been developed over the past decade; very few of them, however, have been based on paleomagnetic data, which still remain scarce. The Chingiz Range in northeastern Kazakhstan provides an opportunity to evaluate the tectonic evolution of the central part of this belt through extensive paleomagnetic studies. In this paper, we report the results from Upper Cambrian andesites and Lower Ordovician tuffaceous sandstones within the Chingiz Range. A high-temperature component (HTC), decaying to the origin, is isolated from Upper Cambrian rocks at eight sites with an easterly and low-intermediate upward direction. This component passes the tilt test and is likely primary. A HTC is also isolated from Lower Ordovician rocks at 11 sites. These site means exhibit a shallow-inclination girdle distribution within the southeast quadrant, likely due to net rotations within the complex structure studied. The inclination-only tilt test is positive, and the best grouping of data is observed at 100% untilting. Also included in our paleolatitudinal analyses are new middle and late Paleozoic paleolatitudes from nearby parts of the Chingiz Range as well as published paleomagnetic data from central and east Kazakhstan. We favor normal polarity of the early Paleozoic results of this paper and conclude that the study area moved northward throughout the Paleozoic. The observed paleolatitudes generally fit the Siberian reference data and hence indicate coherent latitudinal motion of the Boshekul–Chingiz tectonic zone and the Siberian plate.
Keywords: East Kazakhstan; Early Paleozoic; Paleomagnetism; Paleolatitudes; Ural–Mongol fold belt; Paleozoic::Cambrian; Палеозой::Кембрийская